Design Of An E-Learning Environment Using VSAT Technology For ComputerMan University (CMU - Sudan) - Ahmed Hassan, Faris Izzeldin (2007)
This project aims to design an e-learning environment using VSAT technology for ComputerMan University. Thus, this study presents a logical graphical representationsabout the new design, it\'s components and how they interact to deliver learning materials. In addition, this study contributes to knowledge by providing a solid information about VSAT technology and it\'s contribution to e-learning activities.